-5(x-6)+x=8(6-x)

Simple and best practice solution for -5(x-6)+x=8(6-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-6)+x=8(6-x) equation:


Simplifying
-5(x + -6) + x = 8(6 + -1x)

Reorder the terms:
-5(-6 + x) + x = 8(6 + -1x)
(-6 * -5 + x * -5) + x = 8(6 + -1x)
(30 + -5x) + x = 8(6 + -1x)

Combine like terms: -5x + x = -4x
30 + -4x = 8(6 + -1x)
30 + -4x = (6 * 8 + -1x * 8)
30 + -4x = (48 + -8x)

Solving
30 + -4x = 48 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
30 + -4x + 8x = 48 + -8x + 8x

Combine like terms: -4x + 8x = 4x
30 + 4x = 48 + -8x + 8x

Combine like terms: -8x + 8x = 0
30 + 4x = 48 + 0
30 + 4x = 48

Add '-30' to each side of the equation.
30 + -30 + 4x = 48 + -30

Combine like terms: 30 + -30 = 0
0 + 4x = 48 + -30
4x = 48 + -30

Combine like terms: 48 + -30 = 18
4x = 18

Divide each side by '4'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| 20-.2d=.3d+16 | | 9r=20+r | | 5x+4=x-4 | | -24-6x=-54 | | 4/7x=23 | | 37=n+4 | | 11x-6(3+3x)=-53 | | 1x^2+.8*1x^2+.8= | | 56h=56 | | -15+t=(-9) | | 3b+4(b+2)= | | X-1=(-14) | | 9y-4=1 | | 8x-15= | | 6*=36 | | (9x/5)+2x=1 | | X-(-16)=(-16) | | x/7+10.3=-12.1 | | 120+22y=2(105-4y) | | A-10=(-6) | | x^2+1x=42 | | 8u-10.2=15.4 | | 120+22y=2(588) | | -3(r+2)=-55 | | 3+w/31.25=8 | | -3k+10=n+4 | | 120+22y=2(98)(6y) | | x*35.00=6.65 | | A-6=(-30) | | 2x^5=3 | | 3a+2=28+6 | | 7(0)-y=14 |

Equations solver categories